Before sunrise & before sunset [videorecording(DVD)] - Linklater, Richard, 1960-; Hawke, Ethan, 1970-; Delpy, Julie, 1969-; Dobtcheff, Vernon, 1934-; Torres, Louise Lemoine; Pauly, Rodolphe (Warner Home Video, 2009)
Two stranges met by chance, spent a night together in Vienna, and parted before sunrise. Nine years later, Jesse has written a book about the encounter. During his accelerated European book tour, he meets up with Celine in Paris. Before Jesse's flight home, he joins Celine for a picturesque walk around the city and they have an intimate conversation, ending at Celine's apartment. Will they get the chance to fall in love all over again?